Design rules for vertical interconnections by reverse offset printing. (18th January 2018) - Kusaka, Yasuyuki; Kanazawa, Shusuke; Ushijima, Hirobumi
Abstract: Formation of vertical interconnections by reverse offset printing was investigated, particularly focusing on the transfer step, in which an ink pattern is transferred from a polydimethylsiloxane (PDMS) sheet for the step coverage of contact holes. We systematically examined the coverage of contact holes made of a tapered photoresist layer by varying the hole size, the hole depth, PDMS elasticity, PDMS thickness, printing speed, and printing indentation depth. Successful ink filling was achieved when the PDMS was softer, and the optimal PDMS thickness varied depending on the size of the contact holes. This behaviour is related to the bell-type uplift deformation of incompressible PDMS, which can be described by contact mechanics numerical simulations. Based on direct observation of PDMS/resist-hole contact behaviour, the step coverage of contact holes typically involves two steps of contact area growth: (i) the PDMS first touches the bottom of the holes and then (ii) the contact area gradually and radially widens toward the tapered sidewall. From an engineering perspective, it is pointed out that mechanical synchronisation mismatch in the roll-to-sheet type printing invokes the cracking of ink layers at the edges of contact holes. According to the above design rule, ink filling into a contact hole with thickness of 2.5 µ m and radius of 10 µ m was achieved. Contact chain patterns with 1386 points of vertical interconnections with the square hole size of up to 10 µ m successfully demonstrated the validity of the technique presented herein.